Understanding cultural tradition - Zilberman, David B. 1938-1977 (Motilal Banarsidass Publishing House, 2021)
This book is unusual in many respects. It was written by a prolific author whose tragic untimely death did not allow him to finish many other undertakings. Zilberman’s legacy still awaits its true discovery and this book is the third installment to it after The Birth of Meaning in Hindu Thought (Kluwer, 1988) and Analogy in Indian and Western Philosophical Thought (Springer, 2006). Zilberman’s treatment of cultural tradition is unique in its approach, scope and universality for Western philosophical thought. Such applications as linguistics, logic and social analysis, historical and anthropological research, Indology, and all Hindu and Buddhist studies are an integral part of Zilberman’s book. A prophetic leap to largely uncharted territories, this book could be of considerable interest for experts and novices in the field of cultural tradition alike.